(untitled) (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2023)
The development of business in the era of the industrial revolution 4.0 is currently running very rapidly which is marked by developments in the field of internet technology. The existence of internet technology provides great opportunities for new entrepreneurs to promote their businesses, causing many competitors. Therefore, a mechanism is needed. who can coordinate marketing programs so that these programs are synergistically aligned and integrated. This mechanism is referred to as a marketing strategy. Based on the presentation of Munir’s basic food shop marketing strategy, it can be concluded as follows: Internal Environmental Analysis In this internal environment analysis, Munir’s basic food shop is good in terms of promotion but is still lacking in promotion through digital media. The products sold also vary so that customers who subscribe feel quite satisfied. Perseverance in opening shops is also good, but in managing finances it is still not implemented properly. And in customer service still needs to be improved. External Environmental Analysis, The external environmental conditions that affect Munir’s basic food shops are competition between similar trades and the potential entry of new competitors. Due to the emergence of gaps created by existing traders, many plan to look at the business and compete in terms of service and interaction social in the struggle for consumers.